2020
DOI: 10.1155/2020/1849274
|View full text |Cite
|
Sign up to set email alerts
|

Skipping Breakfast Is Associated with an Atherogenic Lipid Profile in Overweight and Obese Prepubertal Children

Abstract: Background. Skipping breakfast has been associated with a higher risk of obesity and cardiovascular (CV) risk factors. However, it is not known if skipping breakfast is also correlated with CV risk factors independently from obesity. The mechanisms explaining the role of skipping breakfast on promoting fat accumulation as well as CV risk are not known. Hormones, in particular, insulin-like growth factor-1 (IGF-1), may potentially play a role in the metabolic profile of breakfast skippers. Aim. This cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…[ 11 ] Expanding beyond heart diseases, a substantial body of research correlates breakfast skipping with a heightened risk of various health issues. This encompasses elevated risks of hypertension, [ 39 , 42 ] diabetes, [ 43 , 44 ] obesity, [ 45 , 46 ] elevated low-density lipoprotein cholesterol, [ 47 , 48 ] dysregulated lipid levels [ 49 ] and metabolic syndrome. [ 50 52 ] Collectively, these conditions are well-recognized risk factors for MI.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Expanding beyond heart diseases, a substantial body of research correlates breakfast skipping with a heightened risk of various health issues. This encompasses elevated risks of hypertension, [ 39 , 42 ] diabetes, [ 43 , 44 ] obesity, [ 45 , 46 ] elevated low-density lipoprotein cholesterol, [ 47 , 48 ] dysregulated lipid levels [ 49 ] and metabolic syndrome. [ 50 52 ] Collectively, these conditions are well-recognized risk factors for MI.…”
Section: Discussionmentioning
confidence: 99%
“…Also, at the level of the liver, thyroid hormone functions in the synthesis and metabolism of fatty acids and cholesterol and a deficiency of thyroid hormone contribute to elevated levels of TC and TG [45]. In addition, insulin-like growth factor-1 (IGF-1) is an important modulator in lipid metabolism [14]. For example, a recent study revealed that IGF-1 had a protective effect against increased levels of LDL-C amongst children and adolescents with short stature [46].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has indicated that prepubertal children who consume breakfast regularly had better lipid profiles than those who skip breakfast (OR 0.17, CI: 0.05 -0.52) [14]. Also, a large study among European adolescents had indicated that breakfast skippers had worse lipid profiles when compared with breakfast consumers [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation